2013
DOI: 10.1155/2013/474272
|View full text |Cite
|
Sign up to set email alerts
|

Licochalcone A-Induced Human Bladder Cancer T24 Cells Apoptosis Triggered by Mitochondria Dysfunction and Endoplasmic Reticulum Stress

Abstract: Licochalcone A (LCA), a licorice chalconoid, is considered to be a bioactive agent with chemopreventive potential. This study investigated the mechanisms involved in LCA-induced apoptosis in human bladder cancer T24 cells. LCA significantly inhibited cells proliferation, increased reactive oxygen species (ROS) levels, and caused T24 cells apoptosis. Moreover, LCA induced mitochondrial dysfunction, caspase-3 activation, and poly-ADP-ribose polymerase (PARP) cleavage, which displayed features of mitochondria-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 38 publications
5
36
0
Order By: Relevance
“…These results agree with a previous report in which LicA inhibited proliferation, increased levels of ROS, and induced apoptosis in T24 cells [98]. This compound also induced mitochondrial dysfunction, caspase-3 activation, and PARP cleavage and caused endoplasmic reticulum (ER) stress-dependent apoptosis [98].…”
Section: Antioxidant Effectssupporting
confidence: 93%
See 1 more Smart Citation
“…These results agree with a previous report in which LicA inhibited proliferation, increased levels of ROS, and induced apoptosis in T24 cells [98]. This compound also induced mitochondrial dysfunction, caspase-3 activation, and PARP cleavage and caused endoplasmic reticulum (ER) stress-dependent apoptosis [98].…”
Section: Antioxidant Effectssupporting
confidence: 93%
“…Evidence suggested that LicA inhibited proliferation by increasing the levels of intracellular ROS because the affects could be attenuated by treatment with the glutathione precursor and antioxidant, N-acetyl-cysteine (NAC) [97]. These results agree with a previous report in which LicA inhibited proliferation, increased levels of ROS, and induced apoptosis in T24 cells [98]. This compound also induced mitochondrial dysfunction, caspase-3 activation, and PARP cleavage and caused endoplasmic reticulum (ER) stress-dependent apoptosis [98].…”
Section: Antioxidant Effectssupporting
confidence: 91%
“…Licochalcone-A, a chalconoid and a type of natural phenol, has been isolated from the root of the licorice plant and has exhibited various pharmacological effects, including antimalarial, anticancer, antibacterial and antiviral properties (7). Furthermore, treatment with licochalcone-A induced apoptosis in various cancer cell types, including oral (36), bladder (37,38), lung (39), gastric (40) and prostate cancer cells (41). In addition, Lico-E, a retrochalone, with various pharmacological effects, including antiparasitic, antibacterial, antioxidative and superoxide-scavenging properties, has been isolated from the root of licorice (24).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that LCA induces apoptosis in HepG2 hepatocellular carcinoma cells through induction of ER stress via a phospholipase C gamma 1-, Ca 2+ -and ROS-dependent pathway (22). Our previous studies have demonstrated that LCA may significantly increase ROS levels and induce apoptosis of T24 human bladder cancer cells (23). However, the underlying molecular mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 96%